Diversidad y tejido social: una aproximación desde el interaccionismo simbólico. - FLORES SOLANO, JOSÉ ALBERTO (CONfines de Relaciones Internacionales y Ciencia Política)
This article shows the basic principles of symbolic interactionism in relation to the concepts of diversity and social fabric, since the search to strengthen the ties between people in a community or society is considered pertinent. As part of this argument and through each postulate, it is stated that just as one learns to live together and behave in a specific way, a person can resignify and change that knowledge regardless of their age or situation, especially through contact and interaction with others, accepting their own diversity and diversity in society, which as a consequence leads to a more solid social fabric. In the final part, an empirically based analysis of the attitude towards diversity is presented with the preliminary results obtained. from an exploratory study to a sample of university students in the area of health sciences, where it is observed that the majority of the sample presents an attitude of openness to diversity but at the same time the scores suggest that this openness may be more of a cognitive and functional type, not necessarily oriented to the search for bonding with diverse people.